Al-Coated Conductive Fibrous Filter with Low Pressure Drop for Efficient Electrostatic Capture of Ultrafine Particulate Pollutants - Choi, Dong Yun; Jung, Soo-Ho; Song, Dong Keun; An, Eun Jeong; Park, Duckshin; Kim, Tae-Oh; Jung, Jae Hee; Lee, Hye Moon (American Chemical Society, 2017)
Here, we demonstrate a new strategy of air filtration based on an Al-coated conductive fibrous filter for high efficient nanoparticulate removals. The conductive fibrous filter was fabricated by a direct decomposition of Al precursor ink, AlH3{O(C4H9)(2)}, onto surfaces of a polyester air filter via:.: a cost-effective and scalable solution-dipping process. The prepared conductive filters showed a low sheet resistance (< 1.0 Omega I sq(-1)), robust mechanical durability and high oxidative stability. By electrostatic force between the charged fibers and particles, the ultrafine particles of 30-400 nm in size were captured with a removal efficiency of similar to 99.99%. Moreover, the conductive filters exhibited excellent performances in terms of the pressure drop (similar to 4.9 Pa at 10 cm s(-1)), quality factor (similar to 2.2 Pa-1 at 10 cm s(-1)), and dust holding capacity (12.5 mu g mm(-2)). After being cleaned by water, the filtration efficiency and pressure drop of the conductive filter was perfectly recovered, which indicates its good recyclability. It is expected that these promising features make the conductive fibrous filter have a great potential for use in low-cost and energy-efficient air cleaning devices as well as other relevant research areas.
Keywords: TRANSPARENT AIR FILTER; ALUMINUM THIN-FILM; FINE PARTICULATE; FILTRATION EFFICIENCY; PM2.5 REMOVAL; FIBER FILTERS; PARTICLE-SIZE; POLLUTION; NANOFIBERS; PERFORMANCE